African agriculture and climate change: new detailed studies to support national agricultural policy makers - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
A CCAFS-supported project led by the International Food Policy Research Institute (IFPRI), and undertaken in collaboration with African partners, is exploring the relationship between changing weather patterns and agricultural production in sub-Saharan Africa. Published as a set of three books, this project’s findings will feed into the design of national and regional policies that support low-income farmers and others most at risk from climate change and variability.